2015
DOI: 10.1080/15332640.2015.1024812
|View full text |Cite
|
Sign up to set email alerts
|

Cultural differences and shame in an expressive writing alcohol intervention

Abstract: The present study evaluates the relationships between shame, culture, and drinking behavior in predicting drinking intentions in the context of an expressive writing intervention. Theory and empirical findings have generally found that shame is maladaptive and can lead to anxiety, depression, and problematic alcohol use. However, research on cultural differences suggests that shame may be differentially damaging to individuals of collectivist, Asian cultures. Previous research evaluating expressive writing as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 65 publications
(73 reference statements)
0
1
0
Order By: Relevance
“…Prior research has shown that shame and guilt distinctly contribute to evaluations of oneself and actions that result in cognitive dissonance and self-discrepancies that produce varying types of symptom manifestations for Veterans when returning from war. These selfconscious emotions are difficult to assess as they are typically used interchangeably (Nazarov et al, 2015 Kubany et al, 1996), or both shame and guilt (Test of Self-Conscious Affect 3-Modified; TOSCA-3; Rodriguez, Young, Neighbors, Tou, & Lu, 2016). For a more comprehensive list of measures assessing shame and guilt see Robins, Noftle, and Tracy (2007).…”
Section: Assessing Shame and Guiltmentioning
confidence: 99%
“…Prior research has shown that shame and guilt distinctly contribute to evaluations of oneself and actions that result in cognitive dissonance and self-discrepancies that produce varying types of symptom manifestations for Veterans when returning from war. These selfconscious emotions are difficult to assess as they are typically used interchangeably (Nazarov et al, 2015 Kubany et al, 1996), or both shame and guilt (Test of Self-Conscious Affect 3-Modified; TOSCA-3; Rodriguez, Young, Neighbors, Tou, & Lu, 2016). For a more comprehensive list of measures assessing shame and guilt see Robins, Noftle, and Tracy (2007).…”
Section: Assessing Shame and Guiltmentioning
confidence: 99%